STRATEGI KEPEMIMPINAN BERBASIS MODAL SOSIAL DALAM MEMBANGUN BUDAYA MUTU PENDIDIKAN - Siswadi Siswadi; Rahman Afandi; Mukroji Mukroji; Guntur Danang Sulistyawan; Siti Sofati (STKIP Pesisir Selatan, 2026)
This study aims to analyse social capital-based educational leadership strategies in improving the culture of educational quality. This study uses a qualitative approach with a literature review design. Data collection was conducted through literature study, then analysed using data reduction techniques, data presentation, and thematic conclusion drawing. The results of the study indicate that social capital-based leadership strategies are realised through: (1) strengthening internal collaboration between teachers and educational staff through learning communities and joint reflection; (2) instilling quality values and organisational norms in the form of collective commitment and mutual cooperation; (3) active involvement of parents and strengthening the role of school committees; and (4) developing external partnerships to expand support networks and resources. These strategies strengthen the structural, relational, and cognitive dimensions of social capital, which have an impact on increasing organisational cohesion, trust, participation, and consistency in the application of quality standards. The research findings confirm that social capital-based educational leadership is capable of transforming a culture of quality from a mere administrative requirement into a collective value that is internalised in the daily practices of the school. The implications of this research emphasise the importance of the headteacher as an agent of social relations and an orchestrator of collaboration in creating a sustainable, adaptive, and participatory culture of quality.